(untitled) (Comprehensive Journal of Science, 2025)
This research aims to diagnose the obstacles hindering the employment of artificial intelligence (AI) strategies in teaching at the Faculty of Physical Education and Sports Sciences, Al-Jafara University, from the perspective of faculty members, and to identify and classify the most prominent of these obstacles according to their impact level. The researcher used the descriptive analytical method and applied a questionnaire to a sample of (20) faculty members at the college. The results revealed multiple obstacles, with financial and material obstacles ranking first with a mean score of (3.750), followed by legislative and administrative obstacles (mean = 3.565), then human obstacles (mean = 3.375), and finally technical and technological obstacles (mean = 3.305). The results also highlighted that the most prominent individual obstacles were "Lack of specialized training" and "Lack of dedicated funding for purchasing software," both with a mean score of (4.15), followed by "Lack of financial support for training" (mean = 4.05). The research concluded that the application of AI strategies requires a comprehensive and integrated approach addressing financial, human, and administrative obstacles simultaneously. It recommended allocating a sufficient budget, developing comprehensive training programs, establishing a clear strategic plan, creating an effective incentive system, simplifying administrative procedures, and supporting the development of smart technologies that support the Arabic language.